Indoor air quality in low carbon buildings in the United Kingdom - Bakri, Miassar (2022)
There is always a demand for energy and the building sector demands a lot of energy. Consequently, due to the increasing amount of energy used in buildings, it is contributing to the increase of Greenhouse gas emission, and it is also contributing to the depletion of natural resources. The answer to this problem was to develop new kind buildings that will ensure that they would consume as little energy as possible. The term low carbon building was used to identify this type of building. However, since low-carbon building is aimed to conserve as much energy as possible it does not guarantee the indoor air condition inside these buildings. Thus, this thesis has studied indoor air quality in two renowned low-carbon buildings that were built using the latest technologies and building standards. The aim of this research was to study whether the implantation of new energy efficient technologies and low-carbon building standards has affected the indoor air quality inside the space. The result of the study has shown that the implantation of new energy efficient technologies did not compromise the indoor air quality inside the space. In fact, the use of new technologies like MVHR has insured the air quality inside the space and allowed for the pollutant inside the space to reach an acceptable level. However, there some issues that were discovered when analysing the data and performing the simulation for the three selected indoor space for this study. The first of these problems is that in the chemistry building, for example, not all areas inside the building have the same indoor air condition. The data from the Open Space Office (OSO) has much better indoor air quality compared to the First Floor Office (FFO). This could show that when designing a low-carbon building all areas inside the space are important and no certain region should be neglected. The second problem was found in the Eco-House Space (EHS) in which the natural ventilation did not provide an adequate indoor air quality condition. The third problem is overheating. the issue of overheating was present in all three indoor spaces which showed that in cold regions like the United Kingdom, there should a well-developed solution that will ensure that indoor air condition in low-carbon building is well kept in all seasons.